Tissue Resident Memory T Cells in the Lungs Protect Against Acute Respiratory Syncytial Virus Infection - Luangrath, Mitchell A. (Immunohorizons, 2021)
Respiratory syncytial virus (RSV) is the leading cause of lower respiratory tract infection in young children. The T cell response plays a critical role in facilitating clearance of an acute RSV infection, and memory T cell responses are vital for protection against secondary RSV exposures. Tissue resident memory (TRM) T cells have been identified as a subset of memory T cells that reside in non-lymphoid tissues and are critical for providing long-term immunity. There is currently limited information regarding the establishment and longevity of TRM T cell responses elicited following an acute RSV infection as well as their role in protection against repeated RSV infections. Here we examined the magnitude, phenotype, and protective capacity of TRM CD4 and CD8 T cells in the lungs of BALB/c mice following an acute RSV infection. TRM CD4 and CD8 T cells were established within the lungs and waned by 149 days following RSV infection. To determine the protective capacity of TRMs, FTY-720 administration was used to prevent trafficking of peripheral memory T cells into the lungs prior to challenge of RSV-immune mice with a recombinant influenza virus expressing either an RSV-derived CD4 or CD8 T cell epitope. We observed enhanced viral clearance in RSV-immune mice suggesting that TRM CD8 T cells can contribute to protection against a secondary RSV infection. Given the protective capacity of TRMs, future RSV vaccine candidates should focus on the generation of these cell populations within the lung to induce effective immunity against RSV infection.